Electrode assembly with high energy density and lithium secondary battery including the same
By using electrode components with specific positive and negative electrode materials in lithium secondary batteries, the shortcomings in existing lithium secondary batteries in terms of energy density and safety are solved, and high energy density, long life and good fast charging efficiency are achieved.
Patent Information
- Application Number
- CN202280003513.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-23
- Filing Date
- 2022-02-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-02-15
AI Technical Summary
Existing lithium secondary batteries have shortcomings in energy density and safety, and it is difficult to meet the needs of high energy density and enhanced safety.
Using a positive electrode mixture layer containing a specific positive electrode active material and a positive electrode additive, and an electrode assembly containing a negative electrode mixture layer containing graphite and silicon-containing particles, the energy density and safety of the battery are improved by adjusting the material ratio and structural design.
The high energy density, long life and good fast charging efficiency of lithium secondary batteries are achieved, while reducing the amount of gas generated during charging and discharging, and improving the stability of the battery.
Smart Images

Figure BDA0003888395120000191 
Figure BDA0003888395120000192 
Figure BDA0003888395120000211
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode assembly having high energy density and a lithium secondary battery including the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0024271 filed on February 23, 2021, the entire contents of which are incorporated herein by reference. Background Art
[0003] In recent years, as concerns about environmental issues have increased, many studies have been conducted on electric vehicles (EVs), hybrid electric vehicles (HEVs), etc. that can replace vehicles using fossil fuels such as gasoline and diesel vehicles, which are one of the main causes of air pollution. Although nickel-metal hydride (Ni-MH) secondary batteries have been mainly used as power sources for EVs, HEVs, etc., lithium secondary batteries with high energy density, high discharge voltage, and output stability are being actively studied, and some of them have been commercialized.
[0004] As the negative electrode material of lithium secondary battery, graphite has been mainly used. However, because graphite has a low capacity per unit mass of 372mAh / g, it is difficult to increase the capacity of lithium secondary battery. In order to increase the capacity of lithium secondary battery, as a non-carbon negative electrode material with a higher energy density than graphite, negative electrode materials forming lithium-metal compounds, such as silicon, tin, its oxide, etc., have been developed and used. Non-carbon negative electrode materials have high capacity, but their initial efficiency is low, thereby consuming a large amount of lithium during initial charging and discharging, and the irreversible capacity loss is large.
[0005] As the positive electrode material for lithium secondary batteries, lithium-containing cobalt oxide (LiCoO2) has been mainly used. In addition, the following substances have also been considered: lithium-containing manganese oxides, such as LiMnO2 with a layered crystal structure, LiMn2O4 with a spinel crystal structure, etc.; and lithium-containing nickel oxide (LiNiO2).
[0006] Although LiCoO2 is currently widely used due to its excellent overall performance such as cycle characteristics, LiCoO2 has low safety and is expensive due to resource limitations of cobalt as a raw material, which limits the use of LiCoO2 as a power source in a large amount in fields such as electric vehicles. In addition, LiNiO2 is difficult to apply to an actual mass production process at a reasonable cost due to the characteristics of its manufacturing method, and lithium plating (Li plating) is induced on the negative electrode due to the gas generated during charging and discharging, which limits the safety and charge / discharge capacity.
[0007] Related technical literature
[0008] Korean Patent Publication No. 10-2014-0046496 Summary of the invention
[0009] [Technical issues]
[0010] An object of the present invention is to provide a lithium secondary battery having high energy density and enhanced safety.
[0011] [Technical solution]
[0012] One aspect of the present invention provides an electrode assembly, the electrode assembly comprising:
[0013] A positive electrode, the positive electrode comprising a positive electrode mixture layer, the positive electrode mixture layer comprising 85 to 95 parts by weight of a positive electrode active material and 0.1 to 5 parts by weight of a positive electrode additive relative to a total of 100 parts by weight of the positive electrode mixture layer, the positive electrode active material comprising lithium nickel cobalt oxide represented by the following chemical formula 1, the positive electrode additive comprising any one or more of lithium cobalt oxide represented by the following chemical formula 2 and lithium iron oxide represented by the following chemical formula 3;
[0014] a negative electrode comprising a negative electrode mixture layer comprising 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si)-containing particles relative to a total of 100 parts by weight of the negative electrode active material; and
[0015] a separator, the separator being interposed between the positive electrode and the negative electrode,
[0016] [Chemical formula 1]
[0017] Li x [Ni y Co z Mn w M 1 v ]O2
[0018] [Chemical formula 2]
[0019] Li p Co 1-q M 2 q O4
[0020] [Chemical formula 3]
[0021] Li a Fe 1-b M 3 b O4
[0022] In Chemical Formula 1 to Chemical Formula 3,
[0023] M 1 is one or more elements selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,
[0024] x, y, z, w, and v respectively satisfy 1.0 ≤ x ≤ 1.30, 0 ≤ y < 1, 0 < z ≤ 0.6, 0 < w ≤ 0.6, and 0 ≤ v ≤ 0.2,
[0025] M 2 is one or more elements selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,
[0026] p and q respectively satisfy 5 ≤ p ≤ 7 and 0 ≤ q ≤ 0.2,
[0027] M 3 is one or more of the following: Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and
[0028] a and b respectively satisfy 4 ≤ a ≤ 6 and 0 ≤ b ≤ 0.5.
[0029] Herein, the positive electrode mixture layer may have a double-layer structure in which a first positive electrode mixture layer and a second positive electrode mixture layer are stacked in sequence on the positive electrode current collector, and may satisfy the conditions of the following Formula 1:
[0030] [Formula 1]
[0031] 0.05 ≤ SCM 1st / SCM 2nd ≤ 0.9
[0032] In Formula 1,
[0033] SCM 1st represents the amount of the positive electrode additive contained in the first positive electrode mixture layer, and
[0034] SCM 2nd represents the amount of the positive electrode additive contained in the second positive electrode mixture layer.
[0035] In addition, the positive electrode mixture layer may satisfy the conditions of the following Formula 2:
[0036] [Formula 2]
[0037] 2 ≤ D 1st / D2nd ≤15
[0038] In formula 2,
[0039] D 1st represents the average thickness of the first positive electrode mixture layer, and
[0040] D 2nd represents the average thickness of the second positive electrode mixture layer.
[0041] In addition, the positive electrode mixture layer may have an average thickness of 100 μm to 200 μm.
[0042] In addition, the positive electrode mixture layer may further include one or more conductive materials selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fiber, and the content of the conductive material may be 0.1 to 10 parts by weight relative to 100 parts by weight of the positive electrode mixture layer.
[0043] In addition, any one or more of the positive electrode mixture layer and the negative electrode mixture layer may contain any one or more binders selected from the following: vinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber and fluororubber.
[0044] In addition, the content of the binder may be 0.1 to 10 parts by weight relative to 100 parts by weight of the positive electrode mixture layer or the negative electrode mixture layer.
[0045] In addition, the negative electrode mixture layer may include 1 to 9 parts by weight or 11 to 19 parts by weight of the silicon (Si)-containing particles relative to 100 parts by weight of the total negative electrode active material.
[0046] In addition, the silicon (Si) particles contained in the negative electrode mixture layer may include one or more of silicon (Si) particles, silicon monoxide (SiO) particles, and silicon dioxide (SiO2) particles. In some cases, the silicon (Si) particles may also include silicon carbide (SiC) particles.
[0047] In addition, the silicon (Si)-containing particles may have an average particle diameter of 0.01 μm to 10 μm.
[0048] Another aspect of the present invention provides a lithium secondary battery including the electrode assembly.
[0049] Still another aspect of the present invention provides a battery module including the lithium secondary battery.
[0050] Beneficial Effects
[0051] Because the electrode assembly according to the present invention includes a positive electrode in which the positive electrode mixture layer includes a specific positive electrode active material and a specific positive electrode additive, and a negative electrode in which the negative electrode mixture layer includes a specific amount of graphite mixed with silicon (Si) particles, the amount of gas generated during charging and discharging of the battery is reduced, and the resistance change rate of the electrode is low even after charging and discharging. Therefore, the lithium secondary battery including the electrode assembly has high energy density, long life and good fast charging efficiency. DETAILED DESCRIPTION
[0052] Hereinafter, the present invention will be described in more detail.
[0053] Electrode assembly
[0054] One aspect of the present invention provides an electrode assembly, the electrode assembly comprising:
[0055] A positive electrode, the positive electrode comprising a positive electrode mixture layer, the positive electrode mixture layer comprising 85 to 95 parts by weight of a positive electrode active material and 0.1 to 5 parts by weight of a positive electrode additive relative to a total of 100 parts by weight of the positive electrode mixture layer, the positive electrode active material comprising lithium nickel cobalt oxide represented by the following chemical formula 1, the positive electrode additive comprising any one or more of lithium cobalt oxide represented by the following chemical formula 2 and lithium iron oxide represented by the following chemical formula 3;
[0056] a negative electrode comprising a negative electrode mixture layer comprising 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si)-containing particles relative to a total of 100 parts by weight of the negative electrode active material; and
[0057] a separator, the separator being interposed between the positive electrode and the negative electrode,
[0058] [Chemical formula 1]
[0059] Li x [Ni y Co z Mn w M 1 v ]O2
[0060] [Chemical formula 2]
[0061] Li p Co 1-q M 2 q O4
[0062] [Chemical formula 3]
[0063] Lia Fe 1-b M 3 b O4
[0064] In Chemical Formulas 1 to 3,
[0065] M 1 is one or more elements selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,
[0066] x, y, z, w, and v respectively satisfy 1.0 ≤ x ≤ 1.30, 0 ≤ y < 1, 0 < z ≤ 0.6, 0 < w ≤ 0.6, and 0 ≤ v ≤ 0.2,
[0067] M 2 is one or more elements selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,
[0068] p and q respectively satisfy 5 ≤ p ≤ 7 and 0 ≤ q ≤ 0.2,
[0069] M 3 is one or more of the following: Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and
[0070] a and b respectively satisfy 4 ≤ a ≤ 6 and 0 ≤ b ≤ 0.5.
[0071] The electrode assembly according to the present invention has a structure including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and the positive electrode has the following form: a positive electrode mixture layer is located on the positive electrode current collector, and the positive electrode mixture layer contains a positive electrode active material that exhibits activity and a positive electrode additive that imparts an irreversible capacity. Specifically, the positive electrode mixture layer contains a lithium nickel cobalt oxide represented by the following Chemical Formula 1 as a positive electrode active material capable of reversibly inserting and extracting:
[0072] [Chemical Formula 1]
[0073] Li x [Ni y Co z Mn w M 1 v O2
[0074] In Chemical Formula 1,
[0075] M1 One or more elements selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0076] x, y, z, w, and v respectively satisfy 1.0 ≤ x ≤ 1.30, 0 ≤ y < 1, 0 < z ≤ 0.6, 0 < w ≤ 0.6, and 0 ≤ v ≤ 0.2.
[0077] The lithium nickel cobalt oxide represented by Chemical Formula 1 is a composite metal oxide containing lithium and nickel, and may contain one or more compounds selected from the following: LiCoO2, LiCo 0.5 Zn 0.5 O2, LiCo 0.7 Zn 0.3 O2, LiNiO2, LiNi 0.5 Co 0.5 O2, LiNi 0.6 Co 0.4 O2, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O2, LiMnO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2.
[0078] For example, the positive electrode active material may contain LiCoO2, LiCo 0.7 Zn 0.3 O2, LiNi 0.5 Co 0.5 O2, or LiNi 0.8 Co 0.1 Mn 0.1 O2 alone or in combination as the lithium nickel cobalt oxide represented by Chemical Formula 1.
[0079] In addition, relative to 100 parts by weight of the positive electrode mixture layer, the content of the positive electrode active material may be 85 to 95 parts by weight, specifically 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight.
[0080] In addition, the positive electrode mixture layer includes a positive electrode additive including any one or more of a lithium cobalt oxide represented by Chemical Formula 2 and a lithium iron oxide represented by the following Chemical Formula 3:
[0081] [Chemical formula 2]
[0082] Li p Co 1-q M 2 q O4
[0083] [Chemical formula 3]
[0084] Li a Fe 1-b M 3 b O4
[0085] In Chemical Formula 2 and Chemical Formula 3,
[0086] M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo,
[0087] p and q satisfy 5≤p≤7 and 0≤q≤0.2 respectively,
[0088] M 3 is one or more selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and
[0089] a and b satisfy 4≤a≤6 and 0≤b≤0.5 respectively.
[0090] Because the positive electrode additive contains excess lithium, it can provide lithium for the lithium consumption that occurs during the initial charge due to the irreversible chemical / physical reaction in the negative electrode. Therefore, the charge capacity of the battery is increased and the irreversible capacity is reduced, thereby improving the life characteristics.
[0091] In the present invention, as a positive electrode additive, any one or more of lithium cobalt oxide represented by Chemical Formula 2 and lithium iron oxide represented by Chemical Formula 3 are included, wherein the lithium cobalt oxide represented by Chemical Formula 2 may include Li6CoO4, Li6Co 0.5 Zn 0.5 O4、Li6Co 0.7 Zn 0.3 O4, etc., and the lithium iron oxide represented by Chemical Formula 3 may include Li2FeSiO4, Li5FeO4, Li6FeO4, etc.
[0092] In addition, the content of the positive electrode additive may be 0.1 to 5 parts by weight, specifically 0.1 to 3 parts by weight or 1 to 3 parts by weight, relative to a total of 100 parts by weight of the positive electrode mixture layer. When lithium cobalt oxide and lithium iron oxide are used in combination, the amount of lithium iron oxide may be 50 to 200 parts by weight relative to 100 parts by weight of lithium nickel cobalt oxide. In the present invention, by adjusting the amount of the positive electrode additive as described above, it is possible to reduce the amount of gas generated during subsequent charging and discharging while maximizing the initial charge capacity of the battery.
[0093] In addition, the positive electrode additive may include a coating on its surface, which may be a carbon coating or a conductive polymer layer. The carbon coating may be formed by carbonizing the organic solvent remaining on the surface when preparing the positive electrode additive; or by treating with glucose, sucrose, galactose, fructose, lactose, starch, mannose, ribose, aldohexose, ketohexose or a mixture thereof separately and then carbonizing. In some cases, the carbon coating may be formed by mixing the prepared positive electrode additive with a carbon material such as graphite, graphene, carbon nanotubes (CNTs), etc. and heat treating the resulting mixture.
[0094] The conductive polymer layer can be formed by mixing 1 to 10 parts by weight of a conductive polymer (eg, polyaniline, polythiophene, polypyrrole or a copolymer thereof) with respect to 100 parts by weight of the positive electrode additive and drying the resulting mixture.
[0095] Furthermore, the coating may have an average thickness of 20 nm or less, specifically 5 nm to 15 nm or 7 nm to 12 nm.
[0096] In the present invention, the conductivity of the positive electrode additive may be improved by introducing the above-mentioned carbon coating layer and / or conductive polymer layer on the surface of the positive electrode additive.
[0097] Furthermore, the positive electrode mixture layer may further include a conductive material and a binder in addition to the positive electrode active material and the positive electrode additive.
[0098] As the conductive material, one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fiber may be included. For example, the conductive material may be acetylene black.
[0099] In addition, the content of the conductive material may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, relative to a total of 100 parts by weight of the positive electrode mixture layer. In the present invention, by controlling the amount of the conductive material within the above range, the deterioration of the charging capacity due to the increase in electrode resistance caused by the small amount of the conductive material can be prevented, and the problem of deterioration of the charging capacity due to the decrease in the amount of the positive electrode active material and the positive electrode additive due to the excessive amount of the conductive material or the problem of deterioration of the fast charging characteristics due to the increase in the load amount of the positive electrode mixture layer can be prevented.
[0100] The binder is a component that helps the mutual bonding of active materials, conductive materials, etc. and the bonding to the current collector, and the binder can be appropriately applied within the range that the electrical properties of the electrode are not degraded. Specifically, the binder may include any one or more selected from the following: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber and fluororubber.
[0101] For example, the binder may be a vinylidene fluoride-hexafluoropropylene copolymer and / or polyvinylidene fluoride.
[0102] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, relative to a total of 100 parts by weight of the positive electrode mixture layer. In the present invention, by controlling the amount of the binder contained in the positive electrode mixture layer within the above range, it is possible to prevent the deterioration of the adhesion of the mixture layer due to a small amount of the binder, or to prevent the deterioration of the electrical properties of the electrode due to an excessive amount of the binder.
[0103] In addition, the positive electrode mixture layer may have a double-layer structure in which a first positive electrode mixture layer and a second positive electrode mixture layer are sequentially stacked on a positive electrode current collector, in which case the positive electrode mixture layer may satisfy the following condition of Formula 1:
[0104] [Formula 1]
[0105] 0.05≤SCM 1st / SCM 2nd ≤0.9
[0106] In formula 1,
[0107] SCM 1strepresents the amount of the positive electrode additive contained in the first positive electrode mixture layer, and
[0108] SCM 2nd Indicates the amount of the positive electrode additive contained in the second positive electrode mixture layer.
[0109] Formula 1 shows the ratio of the positive electrode additive contained in the first positive electrode mixture layer and the second positive electrode mixture layer, and means that the amount of the positive electrode additive contained in the second positive electrode mixture layer (i.e., the amount of lithium cobalt oxide represented by Chemical Formula 2) is greater than the amount of the positive electrode additive contained in the first positive electrode mixture layer. The positive electrode mixture layer according to the present invention may satisfy Formula 1, which is 0.05 to 0.9 (e.g., 0.05≤SCM 1st / SCM 2nd ≤0.9), specifically 0.1 to 0.9 (e.g. 0.1≤SCM 1st / SCM 2nd ≤0.9), 0.2 to 0.8 (e.g. 0.2≤SCM 1st / SCM 2nd ≤0.8), 0.3 to 0.7 (e.g. 0.3≤SCM 1st / SCM 2nd ≤0.7) or 0.4 to 0.8 (e.g. 0.4≤SCM 1st / SCM 2nd ≤0.8). When the positive electrode mixture layer according to the present invention satisfies the condition of Formula 1, the irreversible reaction efficiency of the positive electrode additive during initial charging can be improved.
[0110] In addition, the average thickness of the positive electrode mixture layer may be 100 μm to 200 μm, specifically 100 μm to 180 μm, 100 μm to 150 μm, 120 μm to 200 μm, 140 μm to 200 μm, or 140 μm to 160 μm.
[0111] In addition, when the positive electrode mixture layer has a double-layer structure, the positive electrode mixture layer may satisfy the condition of the following formula 2:
[0112] [Formula 2]
[0113] 2≤D 1st / D 2nd ≤15
[0114] In formula 2,
[0115] D 1st represents the average thickness of the first positive electrode mixture layer, and
[0116] D 2nd represents the average thickness of the second positive electrode mixture layer.
[0117] Formula 2 shows the ratio of the average thickness of the first positive electrode mixture layer to the average thickness of the second positive electrode mixture layer, and means that the average thickness of the first positive electrode mixture layer is greater than the average thickness of the second positive electrode mixture layer. The positive electrode mixture layer according to the present invention can satisfy Formula 2, which is 2 to 15 (for example, 2≤D 1st / D 2nd ≤5), specifically 2 to 13 (e.g. 2≤D 1st / D 2nd ≤13), 2 to 10 (e.g. 2≤D 1st / D 2nd ≤10), 2 to 8 (e.g. 2≤D 1st / D 2nd ≤8), 5 to 10 (e.g. 5≤D 1st / D 2nd ≤10), 4 to 7 (e.g. 4≤D 1st / D 2nd ≤7) or 2 to 5 (e.g. 2≤D 1st / D 2nd ≤5). When the positive electrode mixture layer according to the present invention satisfies the condition of Formula 2, the irreversible reaction efficiency of the positive electrode additive during initial charging can be improved.
[0118] For example, the positive electrode mixture layer may satisfy Formula 1, which is 0.4 to 0.6 (eg, 0.4 ≤ SCM 1st / SCM 2nd ≤0.6), and satisfies Formula 2, which is 2 to 4 (e.g. 2≤D 1st / D 2nd ≤4). In this case, the positive electrode mixture layer may have a structure in which a first positive electrode mixture layer in contact with a positive electrode current collector is formed thickly while a small amount of positive electrode additive is uniformly dispersed, and a second positive electrode mixture layer located on the first positive electrode mixture layer is formed thinly while a large amount of positive electrode additive is uniformly dispersed. Due to this structure, a high charge capacity and an irreversible capacity during initial charging can be simultaneously achieved.
[0119] In addition, the positive electrode can use a positive electrode collector that does not cause chemical changes in the battery and has high conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, the positive electrode collector can be formed with fine concave and convex on its surface to improve the adhesion of the positive electrode active material, and can be used in any of various forms such as films, sheets, foils, nets, porous materials, foams, non-woven fabrics, etc. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the positive electrode collector can be appropriately used in the range of 3 to 500 μm.
[0120] In addition, the negative electrode is manufactured by coating a negative electrode active material on a negative electrode current collector and performing drying and pressing, and may also optionally contain a conductive material, a binder, etc. contained in the positive electrode mixture layer as necessary.
[0121] In this case, the negative electrode active material may include graphite and silicon (Si)-containing particles, and the graphite may include any one or more of natural graphite having a layered crystal structure and artificial graphite having an isotropic structure.
[0122] Silicon (Si) containing particles are particles containing silicon (Si) as a main (semi) metal component, and may include silicon (Si) particles, silicon monoxide (SiO) particles, silicon dioxide (SiO2) particles, or mixtures thereof. In some cases, in addition to silicon (Si) particles, silicon monoxide (SiO) particles, and / or silicon dioxide (SiO2) particles, the silicon (Si) containing particles may also include silicon carbide (SiC) particles, wherein the content of the silicon carbide (SiC) particles may be 0.1 to 20 parts by weight relative to a total of 100 parts by weight of the silicon (Si) containing particles.
[0123] In addition, the particles may have a porous structure including open pores, and the average particle size (D 50 ) may be 0.01 μm to 10 μm. For example, the average particle size (D 50 ) may be 0.01 μm to 8 μm, 0.01 μm to 6 μm, 0.01 μm to 4 μm, 0.01 μm to 2 μm, 0.1 μm to 6 μm, 0.1 μm to 2 μm, 0.1 μm to 0.9 μm, 1 μm to 8 μm, 2 μm to 6 μm, 2 μm to 4 μm, 1 μm to 3 μm or 0.05 μm to 0.9 μm. In the present invention, by reducing the average particle size (D 50 ) is adjusted within the above range, the expansion rate of the silicon (Si) particles during charging can be reduced and the degradation of the battery can be improved.
[0124] In addition, the silicon-containing (Si) particles may have a mixed form of crystalline particles and amorphous particles, and the proportion of amorphous particles may be 50 to 100 parts by weight, specifically 50 to 90 parts by weight, 60 to 80 parts by weight, or 85 to 100 parts by weight relative to a total of 100 parts by weight of the silicon-containing (Si) particles. In the present invention, by controlling the proportion of amorphous particles contained in the silicon-containing (Si) particles within the above range, thermal stability and flexibility can be improved without deteriorating the electrical properties of the electrode.
[0125] In addition, the negative electrode active material may include 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si) particles, relative to a total of 100 parts by weight. More specifically, the negative electrode active material may include 85 to 95 parts by weight, 90 to 95 parts by weight, 88 to 92 parts by weight, or 92 to 94 parts by weight of graphite and 1 to 9 parts by weight, 3 to 7 parts by weight, 11 to 19 parts by weight, or 13 to 17 parts by weight of silicon (Si) particles, relative to a total of 100 parts by weight. In the present invention, by adjusting the amount of graphite and silicon (Si) particles contained in the negative electrode active material within the above range, the amount of lithium consumed during the initial charge and discharge of the battery and the irreversible capacity loss can be reduced, and the charge capacity per unit mass can be increased.
[0126] On the other hand, the negative electrode mixture layer may have a double-layer structure in which a first negative electrode mixture layer and a second negative electrode mixture layer are sequentially stacked on a negative electrode current collector, and the first negative electrode mixture layer and the second negative electrode mixture layer may each be formed in such a manner that graphite and silicon (Si)-containing particles are uniformly mixed, or may be respectively composed of a graphite layer and a silicon (Si) mixed layer (i.e., a layer formed by mixing graphite and silicon (Si)-containing particles). When a graphite layer and a silicon (Si) mixed layer are respectively used as the first negative electrode mixture layer and the second negative electrode mixture layer, since the graphite layer is located between the negative electrode current collector and the silicon (Si) mixed layer, the area in which the silicon (Si) mixed layer as the uppermost layer contacts the liquid electrolyte and / or the electrolyte may be increased, thereby enhancing the diffusion of lithium ions.
[0127] In addition, when a silicon (Si) mixed layer and a graphite layer are used as the first negative electrode mixture layer and the second negative electrode mixture layer, respectively, the silicon (Si) mixed layer is in contact with the negative electrode current collector. In this case, because the silicon (Si) mixed layer is located between the negative electrode current collector and the graphite layer, the loading amount of the negative electrode active material and the average thickness of the negative electrode mixture layer can be reduced, the capture of lithium ions in the silicon (Si) mixed layer during charging can be improved, and the volume expansion of silicon (Si) particles can be suppressed, thereby further improving the life of the battery.
[0128] In addition, the average thickness of the negative electrode mixture layer may be 100 μm to 200 μm, specifically 100 μm to 180 μm, 100 μm to 150 μm, 120 μm to 200 μm, 140 μm to 200 μm, or 140 μm to 160 μm.
[0129] In addition, the negative electrode may include a negative electrode collector that does not cause chemical changes in the battery and has high conductivity. For example, as the negative electrode collector, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used, and copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, similar to the positive electrode collector, the negative electrode collector can be formed with fine concave-convex on its surface to improve the adhesion of the negative electrode active material, and can be used in any of various forms such as films, sheets, foils, nets, porous materials, foams, non-woven fabrics, etc. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode collector can be appropriately applied in the range of 3 to 500 μm.
[0130] In addition, the separator is between the positive electrode and the negative electrode, and an insulating film with high ion permeability and mechanical strength is used. Although there is no particular limitation as long as the separator is commonly used in the art, specifically, a sheet or non-woven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber, polyethylene, etc. can be used, and in some cases, a composite separator in which a porous polymer substrate such as a sheet or a non-woven fabric is coated with inorganic particles / organic particles by an organic binder polymer can be used. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can be used as a separator. In addition, the separator can have an average pore size of 0.01 to 10 μm and an average thickness of 5 to 300 μm.
[0131] On the other hand, the electrode assembly may be housed in a cylindrical battery, a prismatic battery, or a pouch type battery while being wound in the form of a roll, or housed in a pouch type battery in a folded or stack-folded type, but the present invention is not limited thereto.
[0132] Lithium secondary battery
[0133] Another aspect of the present invention provides a lithium secondary battery including the electrode assembly.
[0134] The lithium secondary battery according to the present invention may have a structure in which an electrode assembly is impregnated with a liquid electrolyte containing a lithium salt.
[0135] In this case, the lithium salt-containing liquid electrolyte may be composed of a liquid electrolyte and a lithium salt. As the liquid electrolyte, a nonaqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like may be used.
[0136] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, ethyl propionate, etc. can be used.
[0137] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate-lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, and the like can be used.
[0138] As an inorganic solid electrolyte, for example, Li nitrides, halides or sulfates such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, etc. can be used.
[0139] Lithium salts are substances that are easily soluble in non-aqueous electrolytes, and LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, lithium imide, etc.
[0140] In addition, in order to improve the charge / discharge characteristics, flame retardancy, etc., pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In some cases, halogen-containing solvents such as carbon tetrachloride, trifluoroethylene, etc. may also be included to impart non-flammability, carbon dioxide gas may also be included to enhance high temperature storage characteristics, and fluoroethylene carbonate (FEC), propene sultone (PRS), etc. may also be included.
[0141] Battery Module
[0142] Still another aspect of the present invention provides a battery module including the above-mentioned secondary battery as a unit battery, and also provides a battery pack including the battery module.
[0143] The battery pack can be used as a power source for medium and large-sized devices that require high temperature stability, long cycle characteristics, and high rate characteristics, etc. Specific examples of the medium and large-sized devices include: electric tools driven by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric two-wheeled scooters (E-scooters); electric golf carts; power storage systems, etc., more specific examples of which include HEVs, but the present invention is not limited to these.
[0144] Preferred Implementation
[0145] Hereinafter, the present invention will be described in more detail with reference to Examples and Experimental Examples.
[0146] However, it should be understood that the following embodiments and experimental examples presented herein are given for illustrative purposes only and are not intended to limit the scope of the present invention.
[0147] Examples 1 to 4 and Comparative Examples 1 to 4. Preparation of Electrode Assembly
[0148] N-methylpyrrolidone solvent was added to the homogenizer. To form the first positive electrode mixture layer and the second positive electrode mixture layer, LiNi as the positive electrode active material was weighed as shown in Table 1 below. 0.8 Co 0.1 Mn 0.1 O2, carbon black as a conductive material, PVdF as a binder, and Li6CoO4 as a positive electrode additive were then added to a homomixer and mixed at 3000 rpm for 60 minutes to prepare a slurry for forming a first positive electrode mixture layer and a slurry for forming a second positive electrode mixture layer.
[0149] In addition, natural graphite and silicon (Si) particles as negative electrode active materials and styrene butadiene rubber (SBR) as a binder were prepared, and slurry for forming the first negative electrode mixture layer and slurry for forming the second negative electrode mixture layer were prepared in the same manner as the method for preparing the slurry for forming the positive electrode mixture layer. In this case, the graphite for forming the negative electrode mixture layer was natural graphite, and the average particle size of the silicon (Si) particles was 0.9 to 1.1 μm.
[0150] The prepared slurry for forming the first positive electrode mixture layer was coated on one surface of an aluminum current collector, and then the slurry for forming the second positive electrode mixture layer was coated thereon, followed by drying and pressing at 100° C. to manufacture a positive electrode. In this case, the total thickness of the positive electrode mixture layer was 130 μm, and the total thickness of the manufactured positive electrode was about 200 μm.
[0151] In addition, the prepared slurry for forming the first negative electrode mixture layer was coated on one surface of a copper current collector, and then the slurry for forming the second negative electrode mixture layer was coated thereon, followed by drying and pressing at 100° C. to manufacture a negative electrode. In this case, the total thickness of the negative electrode mixture layer was 150 μm, and the total thickness of the manufactured negative electrode was about 180 μm.
[0152] Thereafter, a separator (thickness: about 16 μm) made of a porous polyethylene (PE) film was interposed between the manufactured positive electrode and negative electrode, and E2DVC as a liquid electrolyte was injected to manufacture a full battery.
[0153] Here, “E2DVC” is a carbonate-based liquid electrolyte and refers to a solution obtained by mixing a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) (volume ratio of 1:1:1) with lithium hexafluorophosphate (LiPF6, 1.0 M) and ethylene carbonate (VC, 2 wt %).
[0154] [Table 1]
[0155]
[0156] Experimental example
[0157] In order to evaluate the performance of the electrode assembly manufactured according to the present invention, an experiment was conducted as follows.
[0158] A) Measurement of gas emissions
[0159] The batteries manufactured according to Example 2 and Comparative Examples 1 to 4 were charged and discharged (formed) once under the conditions of 0.1C / 0.1C at 25°C, and the amount and composition of the gas generated during charging and discharging were analyzed, and the results are shown in Table 2 below.
[0160] [Table 2]
[0161]
[0162] As shown in Table 2, in the case of the electrode assembly according to Example 2 of the present invention, the amount of gas generated during initial charge and discharge of the battery was reduced to less than 103 mL / g.
[0163] From the results, it can be seen that the electrode assembly according to the present invention exhibits a reduced amount of gas generated during initial charge and discharge, thereby improving the stability and efficiency of the battery.
[0164] B) Evaluation of electrical properties
[0165] The battery manufactured according to the embodiment and the comparative example was charged to a final voltage of 4.2 to 4.25V at a charging current of 0.05C at 25°C, and charged to a current density of 0.01C at 0.02V. Then, the battery was discharged to a final voltage of 2V at a discharge current of 0.05C, the charge / discharge capacity and resistance per unit mass of the electrode were measured, and then the measured charge / discharge capacity and the following formula 3 and formula 4 were used to calculate the initial efficiency and capacity retention rate. After the first cycle, charging and discharging were performed at a current of 0.5C and repeated for 400 cycles, and then the resistance of the electrode was measured to calculate the resistance change rate, and the capacity retention rate after 400 cycles of charging and discharging was calculated by the following formula 3. The results are shown in Table 3 below.
[0166] [Formula 3]
[0167] Initial efficiency (%) = (discharge capacity of the first cycle / charge capacity of the first cycle) × 100
[0168] [Formula 4]
[0169] Capacity retention rate (%) = (discharge capacity at the 400th cycle / discharge capacity at the first cycle) × 100
[0170] [Table 3]
[0171]
[0172] As shown in Table 3, it can be seen that the electrode assembly according to the embodiment of the present invention has an effect of improving the performance of the battery.
[0173] Specifically, the electrode assembly of the embodiment exhibited high initial charge / discharge capacity and high efficiency, and the charge / discharge capacity was maintained at a high level even after 400 cycles of charge and discharge.
[0174] According to the results, because the electrode assembly according to the present invention includes a positive electrode in which the positive electrode mixture layer includes a specific positive electrode active material and a specific positive electrode additive and a negative electrode in which the negative electrode mixture layer includes a specific amount of graphite mixed with silicon (Si) particles, the amount of gas generated during charging and discharging of the battery is reduced, and the resistance change rate of the electrode is low even after charging and discharging. Therefore, the lithium secondary battery including the electrode assembly has high energy density, long life and good fast charging efficiency.
[0175] Although the present invention has been described above with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various variations and modifications may be made without departing from the spirit and technical scope of the invention as described in the appended claims.
[0176] Therefore, the technical scope of the present invention should be defined by the appended claims rather than by the detailed description of the specification.
Claims
1. An electrode assembly, the electrode assembly comprising: a positive electrode, the positive electrode comprising a positive electrode mixture layer, relative to a total of 100 parts by weight of the positive electrode mixture layer, the positive electrode mixture layer comprising 85 to 95 parts by weight of a positive electrode active material and 0.1 to 5 parts by weight of a positive electrode additive, the positive electrode active material comprising a lithium nickel cobalt oxide represented by the following Chemical Formula 1, the positive electrode additive comprising any one or more of a lithium cobalt oxide represented by the following Chemical Formula 2 and a lithium iron oxide represented by the following Chemical Formula 3; a negative electrode, the negative electrode comprising a negative electrode mixture layer, relative to a total of 100 parts by weight of the negative electrode active material, the negative electrode mixture layer comprising 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si)-containing particles; and a separator, the separator being interposed between the positive electrode and the negative electrode, [Chemical Formula 1] Li x [Ni y Co z Mr w M 1 v ]O2 [Chemical Formula 2] Li p Co 1-q M 2 q O4 [Chemical Formula 3] Li a Fe 1-b M 3 b O4 In Chemical Formula 1 to Chemical Formula 3, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w and v respectively satisfy 1.0 ≤ x ≤ 1.30, 0 ≤ y < 1, 0 < z ≤ 0.6, 0 < w ≤ 0.6 and 0 ≤ v ≤ 0.2, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, p and q respectively satisfy 5 ≤ p ≤ 7 and 0 ≤ q ≤ 0.2, M 3 is one or more selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and a and b respectively satisfy 4 ≤ a ≤ 6 and 0 ≤ b ≤ 0.
5.
2. The electrode assembly according to claim 1, wherein: The positive electrode mixture layer has a double-layer structure in which a first positive electrode mixture layer and a second positive electrode mixture layer are sequentially stacked on a positive electrode current collector, and satisfies the condition of the following Formula 1: [Formula 1] 0.05≤SCM 1st / SCM 2nd ≤0.9 In Formula 1, SCM 1st represents the amount of the positive electrode additive contained in the first positive electrode mixture layer, and SCM 2nd represents the amount of the positive electrode additive contained in the second positive electrode mixture layer.
3. The electrode assembly according to claim 2, wherein: The positive electrode mixture layer satisfies the condition of the following Formula 2: [Formula 2] 2≤D 1st / D 2nd ≤15 In Formula 2, D 1st represents the average thickness of the first positive electrode mixture layer, and D 2nd represents the average thickness of the second positive electrode mixture layer.
4. The electrode assembly according to claim 1, wherein: The positive electrode mixture layer has an average thickness of 100 μm to 200 μm.
5. The electrode assembly according to claim 1, wherein: The positive electrode mixture layer further comprises one or more conductive materials selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fiber.
6. The electrode assembly according to claim 5, wherein: Relative to 100 parts by weight of the positive electrode mixture layer, the content of the conductive material is 0.1 to 10 parts by weight.
7. The electrode assembly according to claim 1, wherein: Any one or more of the positive electrode mixture layer and the negative electrode mixture layer comprises any one or more binders selected from the following: vinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer, sulfonated ethylene propylene diene monomer, styrene butadiene rubber and fluororubber.
8. The electrode assembly according to claim 7, wherein: Relative to 100 parts by weight of the positive electrode mixture layer or the negative electrode mixture layer, the content of the binder is 0.1 to 10 parts by weight.
9. The electrode assembly according to claim 1, wherein: Relative to a total of 100 parts by weight of the negative electrode active material, the negative electrode mixture layer comprises 1 to 9 parts by weight of the silicon (Si)-containing particles.
10. The electrode assembly according to claim 1, wherein: Relative to a total of 100 parts by weight of the negative electrode active material, the negative electrode mixture layer comprises 11 to 19 parts by weight of the silicon (Si)-containing particles.
11. The electrode assembly according to claim 1, wherein: The silicon (Si)-containing particles comprise one or more of silicon (Si) particles, silicon monoxide (SiO) particles and silicon dioxide (SiO2) particles.
12. The electrode assembly according to claim 11, wherein: The silicon (Si)-containing particles further comprise silicon carbide (SiC) particles.
13. The electrode assembly according to claim 1, wherein: The silicon (Si)-containing particles have an average particle diameter of 0.01 μm to 10 μm. 14 . A lithium secondary battery comprising the electrode assembly according to claim 1 . 15 . A battery module comprising the lithium secondary battery according to claim 14 .
Citation Information
Patent Citations
Electrode of silicon based negative electrode active material, method for producing same, and lithium secondary battery comprising same
KR1020140046496A
Image plate manufacturing method and window manufacturing method including the same
KR1020210024271A
Negative electrode for lithium secondary battery and lithium secondary battery comprising the same
CN107785535A
Lithium secondary battery
CN110651389A